Management of Moral Development for Students - Saprizal Ariga; Muhammad Iqbal; Najmuddin Najmuddin (EDUTEC : Journal of Education And Technology, 2024)
The research in this thesis descriptively explains the management of moral development at Dayah Nurul Islam in Southeast Aceh. The research method used in this study is qualitative with a phenomenological approach. Based on the research findings, it was found that Dayah Nurul Islam in Aceh was established in 1960 by Tengku Abuya Ja’far Sidik bin H. Hasan bin H. Abbas. In its subsequent development, the dayah has expanded in several aspects, including institutional development, curriculum, and facilities. The existence of Dayah Nurul Islam and its role in society is to foster the Muslim community. Therefore, the role of Dayah Nurul Islam in society is as a religious educational institution, a preaching institution, and a social institution. To realize these roles, the management of moral development for students is implemented by integrating modern management systems, including planning, implementation, supervision, and evaluation of moral development for students at Dayah Nurul Islam. The education and teaching system at Dayah Nurul Islam Southeast Aceh follows the modern pesantren system. This is evident from the planning of work programs for each section, the creation of an annual education and teaching calendar according to the work programs that have been prepared, the determination of consultation, coordination, and instruction methods for each section, and the determination of the form, method, and time of reporting for each section. The planning is carried out under the Deputy Director of the Dayah in collaboration with the heads of SMP and MA Nurul Islam Southeast Aceh.